2020
DOI: 10.5755/j01.ee.31.1.23056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Time Allocation for Work and Personal Life among Employed Population in Lithuania from Gender Perspective

Abstract: In this paper, researchers examine the allocation of time for personal life and work. In fact, this phenomenon is particularly relevant in the 21st century because employed people are most commonly faced with many issues related with work-life conflict or work-life imbalance. This kind of problem can occur for both men and women, yet it is noteworthy that the time use features can naturally differ between both sexes: women and men. For this reason, focus of this study lies on the evaluation of work-life balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Document analysis identified two main theoretical concepts regarding the interrelationship between work and private life of employees. These are the concept of work-life conflict (Carlson et al, 2000;Liu & Low, 2011;Hussain & Mujtaba, 2012;Lankeshwara & Wijesekara, 2015;Oosthuizen et al, 2016;Agha et al, 2017;Kim & Kim, 2017;Pejičić & Ranđelović, 2019;Lydeka & Tauraite, 2020;Marič et al, 2021), and the concept of work-life balance (Grzywacz et al, 2002;Lambert & Haley-Lock, 2004;Moore, 2007;Haar et al, 2014;Golubović & Golubović, 2015;Adikaram & Jayatilake, 2016;Fernandez-Crehuet et al, 2016;Stojanović-Aleksić & Bošković, 2017;Marič & Žnidaršič, 2018;Yusuf, 2018;Dilmaghani & Tabvuma, 2019;Apraku et al, 2020). Both of these work-life concepts (conflict and balance) are further researched and analyzed in order to discover their types and forms.…”
Section: Methodology Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Document analysis identified two main theoretical concepts regarding the interrelationship between work and private life of employees. These are the concept of work-life conflict (Carlson et al, 2000;Liu & Low, 2011;Hussain & Mujtaba, 2012;Lankeshwara & Wijesekara, 2015;Oosthuizen et al, 2016;Agha et al, 2017;Kim & Kim, 2017;Pejičić & Ranđelović, 2019;Lydeka & Tauraite, 2020;Marič et al, 2021), and the concept of work-life balance (Grzywacz et al, 2002;Lambert & Haley-Lock, 2004;Moore, 2007;Haar et al, 2014;Golubović & Golubović, 2015;Adikaram & Jayatilake, 2016;Fernandez-Crehuet et al, 2016;Stojanović-Aleksić & Bošković, 2017;Marič & Žnidaršič, 2018;Yusuf, 2018;Dilmaghani & Tabvuma, 2019;Apraku et al, 2020). Both of these work-life concepts (conflict and balance) are further researched and analyzed in order to discover their types and forms.…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…A survey by Lydeka & Tauraite (2020) assessed WLC of 406 male and female employees in Lithuania by comparing the allocation of time between their work and private lives. The main conclusion of this study was that both men and women prioritized work over their private lives.…”
Section: Negative (Inter)relationship Between Work and Private Life O...mentioning
confidence: 99%
“…It is debatable whether there is gender inequality in leisure. While some scholars initially argued that gender equality in leisure could exist [34,35], further studies have shown significant gender inequality in leisure, with men having significantly more leisure time than women being verified by a descriptive statistical analysis of survey data of employed men and employed women in Lithuanian [36], and there is a noteworthy disparity between the quality of leisure time experienced by women and men, with women reporting significantly lower levels based on a multilevel regression of data from the International Social Survey Programme [37]. In-depth interviews with 12 representative mothers show that women adjust their leisure time based on the preferences of their partners and children [38].…”
Section: Micro-influencing Factors Of Leisure Timementioning
confidence: 99%
“…Additionally, women are more likely to wake during the night to provide caregiving. 16 , 17 To date, the majority of studies have focussed only on time use and sleep duration, 16 , 18 , 19 without consideration of the potential impact of time use and time pressure on other gender sleep inequalities, such as sleep quality and sleep difficulties.…”
Section: Introductionmentioning
confidence: 99%